EFFECTIVENESS OF ENGLISH SONGS ON LEARNING ITS VOCABULARY (Konferensiyalar | Conferences, 2024)
This academic article studies the profound impact of music on English vocabulary development and investigates how songs can expand vocabulary, improve pronunciation, and create a deeper grasp of the English language by analyzing various studies and research findings. The paper emphasizes the significance of incorporating music into the language learning curriculum as a valuable instrument for vocabulary growth and linguistic enrichment.